Applications of Fenchel Duality for Vector Optimization Problems - Altangerel, Lkhamsuren (Mongolian Mathematical Journal, 2023)
This paper deals with applications of Fenchel duality for vector optimization problems based on alternative definitions of the conjugate maps and the subgradient for a set-valued map having vector variables (cf. [3]). Some results investigated in Section 4 in [3] allow us to consider applications presented in this paper.